Once-daily etravirine/raltegravir (400/800 mg q24h) dual therapy maintains viral suppression over 48 weeks in HIV-infected patients switching from a twice-daily etravirine/raltegravir (200/400 mg q12h) regimen. (25th October 2020) - Palich, Romain; Allavena, Clotilde; Peytavin, Gilles; Soulie, Cathia; Tubiana, Roland; Weiss, Laurence; Montoya Ferrer, Ana; Duvivier, Claudine; Bouchaud, Olivier; Bottero, Julie; Durand, Aurore; Lê, Minh-Patrick; et al.
Abstract: Background: Etravirine/raltegravir dual therapy has been shown to be highly effective as a twice-daily (q12h) regimen in suppressed HIV-infected patients enrolled in the ANRS-163 study. Objectives: As a once-daily (q24h) regimen is easier for daily life, we aimed to evaluate the capacity of etravirine/raltegravir (400/800 mg) q24h to maintain viral suppression in patients on etravirine/raltegravir q12h. Methods: Patients on a suppressive etravirine/raltegravir q12h regimen for at least 96 weeks were switched to etravirine/raltegravir q24h in this prospective, multicentre, open-label, single-arm study. Primary outcome was the rate of virological failure (VF: confirmed pVL >50 copies/mL, single pVL >400 copies/mL or single pVL >50 copies/mL with ART change) at Week 48 (W48). Secondary outcomes included treatment strategy success rate (no VF and no treatment discontinuation), regimen tolerability, plasma drug concentrations and resistance profile in the case of VF. Results: A total of 111 patients were enrolled, with a median (IQR) age of 57 years (52–62), CD4 count of 710 cells/mm 3 (501–919) and viral suppression for 7.9 years (5.9–10.7). Two patients experienced viral rebound at W24 and W48, leading to a VF rate of 2.0% (95% CI 0.5–7.8) at W48, associated with INSTI resistance in one case. Both had past NNRTI mutations. Ten patients discontinued treatment for adverse events ( n  =   2), investigator or patient decisions ( n  =   3), lost to follow-up ( n  =   3), death ( n  =   1) or pregnancy ( n  =   1). Overall, the strategy success rate was 89% (95% CI 81.5–93.6) at W48. In a subgroup of 64 patients, median (IQR) plasma C 24h concentrations were 401 ng/mL (280–603) for etravirine and 62 ng/mL (31–140) for raltegravir. Conclusions: Switching patients virally suppressed on etravirine/raltegravir q12h to the same regimen but given q24h was highly effective in maintaining virological suppression in HIV-infected patients.